O mapeamento do patrimônio cultural de São Luís de Montes Belos e o papel da educação patrimonial na preservação das referências culturais locais - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The proposition of this research is to present a cultural heritage mapping of the city São Luís de Montes Belos-GO, by means of participation and dialogue with its residents, understood as the ones responsible for indicating the cultural property of public value to local Community. During the process of surveying and inventory, it was always prioritized considering cultural references pointed by local inhabitants, that is, the cultural heritage that makes sense to the group. Therefore, in this report, it was systematized the following inventory categories, listed by monte - belenses inhabitants, the locations, the celebrations, the knowledges, the forms of expression and objects. During the study, heritage education was considered a tool to do an inventory, with the community, local cultural property and, in a similar way, to study local memory with the regional history articulating it with the lives with different subjects and the community. The resulting educational product is a textbook in booth paperback and eBook formats, in which it is presented the cultural heritage of São Luís de Montes Belos, and data on the historic formation and expansion of the city. It is important that history and cultural heritage are present on the school debates, so that the valorization of the memory of each community, and consequently, a feeling of belonging and valorization of its cultural goods are enabled. Thus, the product was created seeking to solve the lack of pedagogical support material for the city schools from São Luís de Montes Belos.
The mapping of the cultural heritage of São Luís de Montes Belos and the role of heritage education in the preservation of local cultural references
Keywords: São Luís de Montes Belos; Educação patrimonial; Bens culturais; Memórias; Heritage education; Cultural property; Memories; CIENCIAS HUMANAS::HISTORIA